Optimal Pipette Resistance, Seal Resistance, and Zero-Current Membrane Potential for Loose Patch or Breakthrough Whole-Cell Recording in vivo - Yan, Linqing; Fang, Qi; Zhang, Xingui; Huang, Bowan (Frontiers in Neural Circuits, 2020)
In vivo loose patch and breakthrough whole-cell recordings are useful tools for investigating the intrinsic and synaptic properties of neurons. However, the correlation among pipette resistance, seal condition and recording time is not thoroughly clear. Presently, we investigated the recording time of different pipette resistances and seal conditions in loose patch and breakthrough whole-cell recordings. The recording time did not change with pipette resistance for loose patch recording (Rp-loose) and first increased and then decreased as seal resistance for loose patch recording (Rs-loose) increased. For a high probability of a recording time ≥ 30 min, the low and high cutoff values of Rs-loose were 21.5 and 36 MΩ, respectively. For neurons with Rs-loose values of 21.5-36 MΩ, the action potential amplitudes changed slightly 30 min after the seal. The recording time increased as seal resistance for whole-cell recording (Rs-tight) increased and the zero-current membrane potential for breakthrough whole-cell recording (MPzero-current) decreased. For a high probability of a recording time ≥ 30 min, the cutoff values of Rs-tight and MPzero-current were 2.35 GΩ and -53.5 mV, respectively. The area under the curve of the MPzero-current ROC curve was larger than that of the Rs-tight ROC curve. For neurons with MPzero-current values ≤ -53.5 mV, the inhibitory or excitatory postsynaptic current amplitudes did not show significant changes 30 min after the seal. In neurons with Rs-tight values ≥ 2.35 GΩ, the recording time gradually increased and then decreased as the pipette resistance for whole-cell recording (Rp-tight) increased. For the high probability of a recording time ≥ 30 min, the low and high cutoff values of Rp-tight were 6.15 and 6.45 MΩ, respectively. Together, we concluded that the optimal Rs-loose range is 21.5 - 36 MΩ, the optimal Rp-tight range is 6.15 - 6.45 MΩ, and the optimal Rs-tight and MPzero-current values are ≥ 2.35 GΩ and ≤ -53.5 mV, respectively. Compared with Rs-tight, the MPzero-current value can more accurately discriminate recording times ≥ 30 min and < 30 min.